HDAC1-3 inhibition increases SARS-CoV-2 replication and productive infection in lung mesothelial and epithelial cells - Trionfetti, Flavia; Alonzi, Tonino; Bontempi, Giulio; Terri, Michela; Battistelli, Cecilia; Montaldo, Claudia; Repele, Federica; Rotili, Dante; Valente, Sergio; Zwergel, Clemens; Matusali, Giulia; Maggi, Fabrizio; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Despite the significant progress achieved in understanding the pathology and clinical management of SARS-CoV-2 infection, still pathogenic and clinical issues need to be clarified. Treatment with modulators of epigenetic targets, i.e., epidrugs, is a current therapeutic option in several cancers and could represent an approach in the therapy of viral diseases. Results Aim of this study was the analysis of the role of histone deacetylase (HDAC) inhibition in the modulation of SARS-CoV-2 infection of mesothelial cells (MCs). MeT5A cells, a pleura MC line, were pre-treated with different specific class I and IIb HDAC inhibitors. Unexpectedly, treatment with HDAC1-3 inhibitors significantly increased ACE2/TMPRSS2 expression, suggesting a role in favoring SARS-CoV-2 infection. We focused our analysis on the most potent ACE2/TMPRSS2 inducer among the inhibitors analysed, MS-275, a HDAC1-3 inhibitor. ACE2/TMPRSS2 expression was validated by Western Blot (WB) and immunofluorescence. The involvement of HDAC inhibition in receptor induction was confirmed by HDAC1/HDAC2 silencing. In accordance to the ACE2/TMPRSS2 expression data, MS-275 increased SARS-CoV-2 replication and virus propagation in Vero E6 cells. Notably, MS-275 was able to increase ACE2/TMPRSS2 expression and SARS-CoV-2 production, although to a lesser extent, also in the lung adenocarcinoma cell line Calu-3 cells. Mechanistically, treatment with MS-275 increased H3 and H4 histone acetylation at ACE2/TMPRSS2 promoters, increasing their transcription. Conclusion This study highlights a previously unrecognized effect of HDAC1-3 inhibition in increasing SARS-CoV-2 cell entry, replication and productive infection correlating with increased expression of ACE2 and TMPRSS2. These data, while adding basic insight into COVID-19 pathogenesis, warn for the use of HDAC inhibitors in SARS-CoV-2 patients.